ANALISIS ZAT WARNA METHANYL YELLOW DALAM MINUMAN ES SIRUP DI KAWASAN KOTA MANADO - Sigar, Esti Santi; citraningtyas, Gayatri; Yudistira, Adithya (UNIVERSITAS SAM RATULANGI, 2012)
Iced beverage syrup is processed in liquid form which has a variety of flavors andcolors. The dye banned methanyl yellow syrup used in drinks because it can cause poisoning,gastrointestinal disorders, and liver tissue damage if consumed in the long term. The purposeof this study was to prove the existence of a dye content of the beverage methanyl yellowsyrup that circulate in the city of Manado. Samples beverage syrup totaling 18 samples weretaken representing 8 districts and the central city of Manado, and then analyzed methanylyellow dye using color reaction, Thin Layer Chromatography and UV-Vis Spectrophotometer.The results showed that in all 18 samples beverage syrup is not identified either dye methanylyellow color reaction method, Thin Layer Chromatography method and UV-Visspectrophotometry. With no identification methanyl yellow dye then make sure the 18samples beverage syrup is free from substances methanyl yellow dye.Keywords : Methanyl Yellow, Iced beverage syrup, Color Reactions, Thin LayerChromatography (TLC), UV-Vis Spectrophotometry, Manado